Addressing Access and Behavioral Constraints through Social Intermediation Services : A Review of Chile Solidario and Red Unidos - Camacho, Adriana; Cunningham, Wendy; Rigolini, Jamele; Silva, Veronica (World Bank, Washington, DC, 2014)
Social programs are often designed under the assumption that individuals make rational decisions that improve their welfare. Yet, informational and behavioral constraints limit the extreme and chronic poor's access and participation in social programs. This paper reviews the implementation and performance of two "social intermediation services" that were designed to address these constraints, improve beneficiaries' access to social programs, and help the poor surmount poverty: Chile Solidario, the first such service in Latin America, and Red Unidos, implemented later in Colombia. The analysis provides insights on key factors influencing performance, cost effectiveness, and the impacts that such services can be expected to have.